Formation of the Nitrative DNA Lesion 8‐Nitroguanine is Associated with Asbestos Contents in Human Lung Tissues: A Pilot Study. Issue 3 (3rd October 2014) - Hiraku, Yusuke; Sakai, Kiyoshi; Shibata, Eiji; Kamijima, Michihiro; Hisanaga, Naomi; Ma, Ning; Kawanishi, Shosuke; Murata, Mariko
Abstract : Formation of the Nitrative DNA Lesion 8‐Nitroguanine is Associated with Asbestos Contents in Human Lung Tissues: A Pilot Study: Yusuke HIRAKU, et al . Department of Environmental and Molecular Medicine, Mie University Graduate School of Medicine— Objectives: Asbestos causes lung cancer and malignant mesothelioma, and chronic inflammation is considered to participate in carcinogenesis. However, biomarkers to evaluate its carcinogenic risk have not been established. Reactive oxygen/nitrogen species are generated in biological systems under inflammatory conditions and may contribute to carcinogenesis by causing DNA damage. In this study, we examined the relationship between the formation of 8nitroguanine (8‐nitroG), a mutagenic DNA lesion formed during inflammation, and asbestos contents in human lung tissues. Methods: We obtained non‐tumor lung tissues from patients with (n=15) and without mesothelioma (n=21). The expression of 8‐nitroG and related molecules was examined by immunohistochemistry, and their staining intensities were semiquantitatively evaluated. Asbestos contents in lung tissues were analyzed by analytical transmission electron microscopy. Results: In subjects without mesothelioma, staining intensities of 8‐nitroG and apurinic/apyrimidinic endonuclease 1 (APE1) were significantly correlated with total asbestos and amphibole contents ( p <0.05), but not with chrysotile content. In mesothelioma patients, their staining intensities were not correlated with asbestos contents. The double immunofluorescence technique revealed that APE1 was expressed in 8‐nitroGpositive cells, suggesting that abasic sites were formed possibly due to the removal of 8‐nitroG. The staining intensities of 8‐oxo‐7, 8‐dihydro‐2'‐deoxyguanosine, an oxidative DNA lesion, and its repair enzyme 8‐oxoguanine DNA‐glycosylase were correlated with age ( p <0.05), but not with asbestos contents in subjects without mesothelioma. Conclusions: This is the first study to demonstrate that 8‐nitroG formation is associated with asbestos contents in human lung tissues. This finding raises a possibility that 8‐nitroG serves as a biomarker that can be used to evaluate asbestos exposure and carcinogenic risk.